Relationship Between Knowledge, Attitudes, and Behavior of Mothers with Nutritional Status in Toddler Children at the Nutrition Recovery Post in Randugunting Village, Tegal City, 2018 - Dewi Sulistyoningrum; Tuti Hadiyanti (Dian Nuswantoro Semarang, 2019)
Background: Nutrition problems are one of the public health problems that have never been completely overcome in the world. Based on the fact that the discovery of toddlers with malnutrition is still a problem that cannot be dealt with properly, so researchers are interested in analyzing the relationship between knowledge, attitudes and behavior of mothers with nutritional status in children under five at the nutrition recovery post in Randugunting Village, Tegal City.Method: This study used an observational analytic study design with a cross sectional approach. The population of all mothers who have children under five with poor nutritional status in the Nutrition Recovery Post in Randugunting Village, Tegal City. The research sample was obtained as many as 15 samples using the purposive sampling method.Results: The results of the statistical test showed that there was a relationship between knowledge and nutritional status in children under five with p = 0.044. While maternal attitudes p = 0.119 and maternal behavior p = 1,000 did not have a significant relationship with nutritional status in children under five.Conclusion: From the results of the analysis that has been done it can be concluded that the knowledge variable has a significant relationship to nutritional status in children under five, while the attitude and behavior variables do not have a significant relationship to nutritional status in children under five. Suggestions for public health centers to improve programs that can restore good nutritional status for toddlers, especially mother's knowledge on improving toddler nutrition.Â Keywords: Nutrition, Knowledge, Attitude, Behavior